Helping Teens Overcome Anxiety Episodes in Project Work: The Power of Reframing. Issue 2 (March 2021) - Orson, Carolyn N.; Larson, Reed W.
Overwhelming challenges in youth program projects (e.g., arts, leadership, science, technology, engineering, and mathematics [STEM]) can create intense anxiety for adolescents that disrupts engagement in their work. This study examines how experienced program leaders respond to these episodes to help youth overcome anxiety. We conducted semi-structured interviews with 27 veteran leaders from high-quality youth programs about their experiences with these situations. Programs primarily served Latinx, African American, and European American youth (ages 11–18). We utilized grounded theory analysis to examine leaders' descriptions of the situations, their strategies, and the goals of those strategies. Leaders' most frequent response was reframing —providing youth new cognitive frames to understand anxiety-eliciting situations, reduce anxiety, and restore motivation. We identified three types of reframing strategies. First, reframing youth's understanding of their abilities entailed providing youth new perspectives for enhancing their conceptions of their competencies in the work. Second, reframing youth's understanding of challenge involved suggesting new frameworks for youth to assess and control work challenges. Third, reframing emotion involved helping youth understand anxiety as normal and as a tool for problem-solving. The findings also suggest these strategies help youth learn skills for managing situations that create anxiety in future work.